2004
DOI: 10.1093/ajcn/80.2.475
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric assessment of 10-y changes in body composition in the elderly

Abstract: Skinfold thicknesses cannot be used to assess changes in body fat mass because of age-related fat redistribution. Higher levels of physical activity can attenuate the decline in appendicular lean tissue expected over 10 y. Waist and thigh girths, rather than skinfold thicknesses, should be considered for use in longitudinal studies in the elderly because the changes in these girths capture increased abdominal adiposity and sarcopenia, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
171
0
22

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 300 publications
(203 citation statements)
references
References 31 publications
10
171
0
22
Order By: Relevance
“…Several studies showed age-related decline in height, probably because of spinal deformity with thinning of the inter-vertebral discs as well as loss of vertebral body height due to osteoporosis. 17,[35][36][37] The cumulative height loss from age 30 to 70 y has been demonstrated to average about 3 cm for men and 5 cm for women; by the age 80 y it increased to 5 cm for men and 8 cm for women. 35 Substantial age-related height loss was also observed in a prospective study conducted in Elderly European born in 1913-1918.…”
Section: Obesity and Aging M Zamboni Et Almentioning
confidence: 99%
“…Several studies showed age-related decline in height, probably because of spinal deformity with thinning of the inter-vertebral discs as well as loss of vertebral body height due to osteoporosis. 17,[35][36][37] The cumulative height loss from age 30 to 70 y has been demonstrated to average about 3 cm for men and 5 cm for women; by the age 80 y it increased to 5 cm for men and 8 cm for women. 35 Substantial age-related height loss was also observed in a prospective study conducted in Elderly European born in 1913-1918.…”
Section: Obesity and Aging M Zamboni Et Almentioning
confidence: 99%
“…Nossos achados estĂŁo de acordo com estudos prĂ©vios que tem demonstrado mudanças relacionadas Ă  idade que contribuem para alteraçÔes na composição corporal, tais como aumento da massa gorda (MG) e diminuição da massa magra (MM) e perda de altura causada pela compressĂŁo dos corpos vertebrais e cifose 16,17 . No entanto, as alteraçÔes observadas no presente estudo ocorreram indepedentes do avanço da idade, demonstrando o efeito da atividade sistematizada realizada durante 12 semanas.…”
Section: Discussionunclassified
“…3 Indeed these studies have evidenced a redistribution of fat from subcutaneous to visceral depots that occurs from middle age until old ages, which leads to a preferential visceral WAT expansion during lifetime. 3,5,6 As a consequence, a relative increase in visceral fat with aging has been associated to metabolic dysfunction and related maladies. 7 However it is important to note again that WAT expansion manifests already in middle age both in human and mouse, occurring much earlier than the onset of metabolic disease.…”
Section: General Considerations About Age-dependent Obesitymentioning
confidence: 99%